Autonomia universitária: um estudo sobre as universidades estaduais do Paraná entre os anos de 2015 e 2018 - Goetten, Rafael de Paula (2021)
This investigation, whose field of study is the State Institutions of Higher Education (known in Brazil by the anacronym IEES) of Paraná, was developed from the issue of university autonomy in the period from 2015 to 2018, during the government term of Carlos Alberto Richa (Brazilian Social Democracy Party – PSDB). Initial studies for the elaboration of the research proposal indicated that, in this period, several attacks on the university autonomy of the IEES were carried out, resulting in the interest in studying this context. The research has a documentary character, based on government sources from official bodies (government and IEES from Paraná) and state, national and international institutions (labor union sections of IEES’s professors and World Bank’s reports), using quantitative and qualitative methodological aspects. The theoretical framework, focused on the historical-dialectical materialism, especially the contributions of Antonio Gramsci and his definitions of superstructure and structure, modern State, hegemony, civil and political society, resulted in the identification of the object categories: university autonomy, authoritarian-regulatory state and counter-hegemonic movements led by the labor union sections. The research is organized into three chapters. In the first, it was sought to analyze the Brazilian historical-political situation, in order to establish relationships between the influences of neoliberal ideology in the promotion of public policies aimed at the Higher Education, amid the authoritarian and conservative context of the country, in addition to its reflections on the process of formation of the state of Paraná and, consequently, in its university system. In the second chapter, the studies were directed on two fronts: document analysis, based on academic productions on the subject studied; then, attention turned to the seven selected IEES (UEPG, UEL, UEM, UNIOESTE, UNICENTRO, UNESPAR and UENP), in order to present their structural and organizational aspects. Regarding university autonomy, two institutional documents of each university were examined, the Institutional Statute and the Institutional Development Plan, in order to understand the interpretation and direction given by each institution on the subject. Finally, in the third chapter, the issue of university autonomy of the Paraná IEES in the government of Carlos Alberto Richa (PSDB), in his second term, was explored, and the main documents that prove governmental interference in academic spaces were analyzed; in contrast, it was also presented the labor union reactions to the government’s attitudes. The results obtained allowed to conclude that: a) university autonomy, in addition to being relative, assumes an authoritarian and fragmented profile; b) the state of Paraná followed the Brazilian situation and promoted a mixture between a conception of State that meets the wishes of the economic capital, under the guidance of international organizations, especially the World Bank, allied to an arbitrary, violent and regulatory profile; c) the IEES from Paraná, even promoting discourses that value the processes of university autonomy, act in line with neoliberal demands; d) one of the main fronts of reactions to the attacks against Paraná state universities are carried out by the union movements.